Effect of Reference Height Control System on CPG Networks for Quadruped Hopping Robot - Anuar , Mohamed Kassim; Abdul rashid, Mohd Zamzuri; Mohd Rusdy , Yaacob; Abas, Norafizah (2013)
In this paper, the collaboration of CPG networks with the feedback control system which are composed with the maximum hopping height detector and the Proportional Integral (PI) controller as an engineering application for the CPG network is proposed with the developed control systems. By adding the feedback loop through the feedback controller, the developed quadruped hopping robot not only can generate the continuous hopping performances but also can control the desired hopping height. As the result, the effectiveness of CPG networks to keep the stability of the developed quadruped hopping robot besides of confirming the validity of using reference height control system to generate hopping capability at different reference height, respectively.